Pendampingan Penulisan Artikel Ilmiah dari Hasil Penelitian bagi Guru Matematika SMK Kota Kediri - Lucky Tri Oktoviana; Dahliatul Hasanah; I Made Sulandra; Susiswo Susiswo; Trianingsih Eni Lestari; Rini Nurhakiki (University of Merdeka Malang, 2020)
Doing research and publication in the form of scientific article is not part of teachers’ duties as an educator. Conducting research particularly class action research, however, is a necessity for teachers to solve some problems experienced in class. The needs to publish an article from research result emerges from the importance of sharing research result conducting in class. This research result may solve similar problems happened in other classes and experinced by other teachers. High school mathematics teachers in Kediri city encounter difficulties in transforming research result into a scientific article. This community service program provides a training and accompaniment in writing a scientific article. This program involves some activities, i.e. (1) elucidating the structure of scientific articles and its description, (2) giving examples of scientific articles from research results, (3) practicing in writing scientific article, and (4) presenting article results from practice section. This program is expected to encourage high school mathematics teachers in Kediri city to have a scientific article and to publish the article in seminars or scientific journals.DOI: https://doi.org/10.26905/abdimas.v5i2.3820